Preparation, characterization and digestive mechanism of plant-derived oil bodies-based oleogels structured by chitosan and vanillin. (March 2023) - Farooq, Shahzad; Ahmad, Muhammad Ijaz; Zhang, Yipeng; Chen, Meiyu; Zhang, Hui
Abstract: This study has explored a facile approach to structure oleogels using plant-derived oil bodies (OBs) as oil droplets that were electrostatically coated by chitosan as an outer layer, followed by vanillin induced cross-linking of the coated droplets. The electrostatic interaction, Schiff base reaction and hydrogen bond cross-linkages were the main driving forces between the OBs, chitosan and vanillin for the construction of oleogels, as shown by the ζ-potential, FTIR and fluorescence spectroscopy results. Morphological analysis demonstrated that chitosan coating on the OBs prevented the oiling-off of oleogels, while vanillin addition resulted in closely packed 3D-network structures. From differential scanning calorimetry analysis, it was exhibited that the peak temperature and enthalpy of oleogels increased as the chitosan or vanillin concentration increased. Macro-properties showed that the cross-linked oleogels were thermally stable with excellent thixotropic recovery ability (97.6%), as well as, had higher gel strength ( G ′ > 18, 000 Pa) and gel hardness (13.10 N) values, suggesting that interfacially adsorbed chitosan and interconnected vanillin networks together contributed to the development of solid oleogel structures. Moreover, lipid digestion kinetics revealed that cross-linking slowed down the free fatty acids release rate of oleogels, which may have been due to: i) compact coating layer formed by chitosan partially restricted the interfacial displacement by enzymes, ii) integrated networks induced by vanillin reduced the void spaces available for the diffusion of lipases and bile salts, which were confirmed by microstructural digesta. This study provides a novel strategy for the production of edible oleogels using OBs to potentially replace solid fats. Graphical abstract: Image 1 Highlights: Plant-derived OBs-based oleogels were successfully structured with chitosan and vanillin. Chitosan-coated OB oleogels were cross-linked via vanillin-induced Schiff base reaction and hydrogen bond interactions. Increasing chitosan or vanillin concentration led to an increase in the oleogel strength. Presence of chitosan decreased the rate and degree of hydrolysis of the oleogel by acting as a barrier to the diffusion of pepsin. Vanillin-induced interconnected structures slowed down the disintegration of oleogels during lipolysis.